“A viagem de volta” : a formação profissional em serviço social no estado do Rio Grande do Sul - Hoepner, Charles Machado (2017)
The present production has as theme the professional qualification in social work, especially, with respect to its conformation in the state of Rio Grande do Sul, locus of conducting this research. Aiming “analyze how it has been giving the professional training of social worker in Higher Education Institutions of mesoregions state of Rio Grande do Sul to understanding the process and peculiarities that conform it” this production sought to demonstrate how it has been professional training of the Social Workers gauchos in times advancement of neoliberalism whose impacts on the Higher Education Policy contribute to non-characterization of the university as a social institution. In this context, the university becomes a social organization which aims to meet the demands from the Market. Using Marx's critical social theory as a foundation, this mixed type survey has as subjects to the research seven gaúchas universities, one belonging to each mesoregion of the state of Rio Grande do Sul. Therefore online questionnaires were sent to the coordinating teachers of five Social Works curses being one belonging to each mesoregion of the state with open and closed questions, having as a discussion the process of professional training in Social Work in these institutions. Furthermore, 20 questionnaires were applied with students from Social Work courses, with the aim of identifying the profile of the student attending Social Service in the state. Finally, two interviews were conducted with two course coordinators, having as criterion of choice the private course and the oldest public course in the state of Rio Grande do Sul. Guided further in the documentary and bibliographic research we identified that the professional formation in Social Service in the state of Rio Grande do Sul accompanies the changes that have been taking place in the Brazilian Social Service, especially with regard to the considerable increase in Social Work courses in the distance modality and the primacy of the offer of private courses of Social Work. We also identify that, although the courses affirm dialogue with the Curriculum Guidelines of the ABEPSS in the process of building their political-pedagogical projects what is observed is a misunderstanding of the content of these Guidelines and a partial use in the construction of the curricular of these courses. Finally, it should be noted that, although most curricular observe the theoretical advances and politicians present in the Curricular Guidelines of the we still have resumes with conservative traits that predate the 1996 formulation which contributes to the weakening of professional training of social workers in Rio Grande do Sul.